Assessment of an intervention aimed at early discontinuation of intravenous antimicrobial therapy in a Brazilian University hospital - Bonella,Gislaine Ferraresi (2016)
Abstract Many interventions demonstrate success in adapting the duration of intravenous antibiotic therapy, but few studies have been conducted in developing countries. The aim of this study was to evaluate the effectiveness of an intervention in the induction of early discontinuation of intravenous antimicrobial therapy and/or its switch to oral therapy. The study employed a before–after intervention design that consisted of displaying a message in the computerized prescription on the third day and suspension of the prescription on the fifth day of intravenous antimicrobial therapy. A total of 465 patients were followed during the control period (CP) and 440 in the intervention period (IP). The intravenous therapy was switched to oral therapy for 11 (2.4%) patients during the CP and 25 (5.7%) in the IP (p = 0.011), and was discontinued for 82 (17.6%) patients during the CP and 106 (24.1%) in the IP (p = 0.017). During the IP there was a significant increase of patients who had their antimicrobial treatment discontinued before the seventh day of intravenous treatment, 37.40% (49/131) in the IP and 16.13% (15/93) in the CP (p = 0.0005). The duration of intravenous antimicrobial therapy decreased by one day, but it was not significant (p = 0.136). It is concluded that the proposed intervention is effective in promoting the early discontinuation of antimicrobial treatment and/or switch to oral therapy. As long as a computerized system for prescription already exists, it is easy and inexpensive to be implemented, especially in hospitals in developing countries.